2016
DOI: 10.1051/e3sconf/20161000031
|View full text |Cite
|
Sign up to set email alerts
|

Methane rich gasification of wood pellets

Abstract: Abstract. In the work there are shown the results of experimental studies on methane rich gasification of pinewood pellets in Bio-CONOx technology. The experiment was carried out on a laboratory scale gasifier (5 kW), which design features allow producing a high quality gas with a high methane content. In the results there was identified the impact of the quantity of Bio-CONOx on the amount of flammable gas compounds (methane, hydrogen and carbon monoxide) in the synthesis gas and the gas calorific value. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…As can be seen, CO is the main combustible gas in all cases, with concentrations ranging from 9-35 vol%. This study's CO concentrations are comparable and within the same range as those derived from other studies [30][31][32]34,[36][37][38]]. In the above-mentioned studies, the concentration of H 2 ranged from 2-35 vol% compared to a concentration from 4.0 to 4.3 vol% obtained in the producer gas from the gasification of the currently studied WB, which was similar to the results of Joka et al, Inayat et al, and Poskrobo et al [31][32][33].…”
Section: Producer Gas Compositionsupporting
confidence: 87%
See 3 more Smart Citations
“…As can be seen, CO is the main combustible gas in all cases, with concentrations ranging from 9-35 vol%. This study's CO concentrations are comparable and within the same range as those derived from other studies [30][31][32]34,[36][37][38]]. In the above-mentioned studies, the concentration of H 2 ranged from 2-35 vol% compared to a concentration from 4.0 to 4.3 vol% obtained in the producer gas from the gasification of the currently studied WB, which was similar to the results of Joka et al, Inayat et al, and Poskrobo et al [31][32][33].…”
Section: Producer Gas Compositionsupporting
confidence: 87%
“…This study's CO concentrations are comparable and within the same range as those derived from other studies [30][31][32]34,[36][37][38]]. In the above-mentioned studies, the concentration of H 2 ranged from 2-35 vol% compared to a concentration from 4.0 to 4.3 vol% obtained in the producer gas from the gasification of the currently studied WB, which was similar to the results of Joka et al, Inayat et al, and Poskrobo et al [31][32][33]. However, some studies of WB gasification in fixed-bed reactors by Brynda et al and Bhatia et al [34,37] also demonstrated higher concentrations of H 2 (16-25 vol%).…”
Section: Producer Gas Compositionsupporting
confidence: 87%
See 2 more Smart Citations